Improving Care for Critical Care Patients by Strategic Alignment of Quality Goals With a Physician Financial Incentive Model. Issue 1 (January 2021) - Shittu, Atinuke; Hannon, Emily; Kyriacou, Jonathan; Arnold, Desiree; Kitz, Michael; Zhang, Ziya; Chan, Christy; Kohli-Seth, Roopa
Abstract : Background and Objectives: The passage of the Affordable Care Act has ignited a shift from the pay-for-performance model to value-based care with a particular relevance in critical care settings. Provider incentive programs are widely considered as a means to reward providers based on the achievement of preset quality metrics. This article aims to demonstrate the effects of a provider incentive program in the critical care delivery system in a large academic center in the Northeastern United States. Methods: This article describes the results of a retrospective analysis of a performance-driven quality improvement initiative at a critical care facility of an academic medical center using a quasi-experimental pre-/posttest design. A set of quality measures was selected as outcome metrics. Selection criteria for the process measures are as follows: (i) the metric goals should be influenced by the physician's input to a large degree; (ii) the measure must be transparent and accessible within the hospital-wide data reporting system; (iii) the metric that required group effort and interdisciplinary collaboration to achieve; and (iv) the measure must directly affect patient outcome. The outcome metrics are central line–associated bloodstream infections (CLABSIs) and catheter-associated urinary tract infections (CAUTIs), standardized infection ratio (SIR), Foley catheter and central line utilization standardized utilization ratio (SUR), hand hygiene compliance, and adherence to respiratory recovery pathway goals. These metrics were tracked from for 3 years with success defined as achieving set benchmarks for each metric. Results: The average CLABSI SIR and CAUTI SIR across all intensive care units (ICUs) decreased by 44% ( P = .05) and 87% ( P = .02) over 3 years as well as the central line and Foley catheter utilization falling by 41% and 30%, respectively. Hand hygiene compliance in the ICUs improved for the same period by 27 percentage points, as did compliance with the respiratory recovery pathway program by 4 percentage points. Conclusion: The use of a physician-driven financial incentive model in a critical care setting measured by outcome metrics dependent on physician input is successful with rigorous implementation and careful evaluation.